Subjective well-being components in the HEXACO personality framework - Pocrnić, Martina; Bratko, Denis (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Subjective well-being (SWB) is a multidimensional construct composed of (i) a cognitive component, which includes an assessment of life satisfaction, and two affective components, (ii) positive affect (PA) and (iii) negative affect (NA). These three components are theoretically independent and they may have different relations with other constructs. In various studies, SWB is often associated with personality traits, which have been dominantly operationalized within five-factor frameworks. The aim of the present study is to examine the relationship between SWB components and their relations with personality traits defined within the six-factor personality model, HEXACO. The study was conducted on a sample of 830 young adults (63% women) who completed the Satisfaction with Life Scale, the Positive and Negative Affect Schedule and the HEXACO-PI-R. The results show that the three SWB components are moderately correlated. Extraversion correlated most strongly with all three components, as well as the Conscientiousness, but with smaller effect sizes, while Emotionality had only a significant positive correlation with NA. The findings of this study highlight the importance of distinguishing SWB components, but also the structural differences of the HEXACO personality model compared to five-factor models.